A study of subclinical hypothyroidism during pregnancy - DR.V.ARUNA, (International Journal of Pharma and Bio Sciences, 2019)
This study was designed to evaluate thyroid status in pregnant women as routine antenatal checkup as suggested by the Health and Family Welfare department, Government of India. The present study was carried out to determine the incidence of Hypothyroidism among pregnant women in tertiary care centre at GGH, Guntur, AP. 240 subjects were selected for the study after careful screening for thyroid disorders, PIH, GDM or other endocrine diseases. Their venous blood samples were analysed for TSH, Total T3 and Total T4. The number of subjects in each trimester were 80. The results showed that 1/3rd of the study group fall in the category of subclinical hypothyroid when S.TSH of >2.5µIU/ml was considered as significant rise. There was significant correlation of mean TSH of SCH and Euthyroid group with a P value <0.001. Trimester-wise mean TSH values of SCH & Euthyroid showed significant difference (ANOVA)P value <0.00001. 2-tailed paired ‘t’ test showed significant correlation of mean TSH in 1st &2nd trimester P value <0.002 but significance was negligible in 2nd &3rd trimesters. There was conclusive evidence to prove that pregnant women were prone to develop hypothyroidism can prove detrimental to maternal and fetal health. Thyroid status needs to be evaluated in all pregnant women irrespective of risk factors.